2011
DOI: 10.5539/ijbm.v6n2p147
|View full text |Cite
|
Sign up to set email alerts
|

Are Human Resource Departments Really Important? An Empirical Study on Malaysian Small and Medium Enterprises (SMEs) in the Service Sector

Abstract: The intention of this study is to examine the significant differences in terms of employees' job satisfaction and firms' performance for Malaysian SMEs that has their own Human Resource (HR) department against organisations who doesn't have their own HR department. Besides that, this study provides more insight towards Malaysia's Human Resource Management practices based on 43 SMEs in the service sector. FindingsThe finding of the study reveals that there are significant differences between organisations with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…This response rate was achieved only after a great deal of effort and hard work. In comparison to other research, the response rate was very high due to the use of a self-administered questionnaire (Ahmed, Hassan, & Taha, 2004;Osman, CF, & Galang, 2011;Zakaria, Zainal, & Nasurdin, 2011). The sample size of 381 was deemed sufficient in PLS to achieve an acceptable degree of statistical power.…”
Section: Response Ratementioning
confidence: 81%
“…This response rate was achieved only after a great deal of effort and hard work. In comparison to other research, the response rate was very high due to the use of a self-administered questionnaire (Ahmed, Hassan, & Taha, 2004;Osman, CF, & Galang, 2011;Zakaria, Zainal, & Nasurdin, 2011). The sample size of 381 was deemed sufficient in PLS to achieve an acceptable degree of statistical power.…”
Section: Response Ratementioning
confidence: 81%
“…Our results contribute to the literature as they show that not all SMEs implement a learning culture equally and that a greater learning culture is associated with a particular set of characteristics, such as size (having more than 100 employees), sector (being part of the manufacturing and public services sectors), unionization and requirements under the Act to promote workforce skills development and recognition. These SMEs may be better equipped for talent and knowledge management, among other things, because of the high proportion of respondents who are HR directors or managers, as the past study showed having an HR department is associated with employees’ training and development (Osman et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Human resources are strategic resources essential to the organization as knowledge, skills, abilities, behaviours, and interaction of the employees can influence organizational performance (Osman et al, 2011). In a competitive global business environment, organizations increasingly consider their employees a critical asset that enables them to sustain their competitive edge.…”
Section: Hphrps and Business Performance-linkagementioning
confidence: 99%